2010
DOI: 10.1159/000311014
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Multifocal Leukoencephalopathy Deaths in the USA, 1979–2005

Abstract: Background: Progressive multifocal leukoencephalopathy (PML) is a neurological disease most often seen among immunosuppressed patients. The incidence of PML increased with an increasing incidence of HIV/AIDS. We describe recent trends and the epidemiology of PML-associated death in the era of highly active antiretroviral therapy (HAART). Methods: National multiple-cause-of-death data for the USA were used to identify records with PML listed as a cause of death during 1979–2005. Age-adjusted PML-associated deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the pre-human immunodeficiency virus era PML was anecdotally reported in some patients with myelolymphoproliferative disorders or other forms of cancer, but its incidence significantly increased with the advent of acquired immunodeficiency syndrome, affecting 0.7/1000 persons/year [3]. After the introduction of antiretroviral treatment the incidence (0.07/1000 persons/year) [3] and the mortality of the disease reduced significantly [4,5]. Recently, several cases of PML related to the use of new immunomodulatory compounds for the treatment of several dysimmune diseases were reported, leading to an urgent need for the identification of risk factors and disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…In the pre-human immunodeficiency virus era PML was anecdotally reported in some patients with myelolymphoproliferative disorders or other forms of cancer, but its incidence significantly increased with the advent of acquired immunodeficiency syndrome, affecting 0.7/1000 persons/year [3]. After the introduction of antiretroviral treatment the incidence (0.07/1000 persons/year) [3] and the mortality of the disease reduced significantly [4,5]. Recently, several cases of PML related to the use of new immunomodulatory compounds for the treatment of several dysimmune diseases were reported, leading to an urgent need for the identification of risk factors and disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide Danish study of HIV-associated PML found that the incidence rates declined from 3.3 per 1,000 person-years in 1995-1996 (pre-HAART era) to 1.8 per 1,000 personyears in 1997-1999 (early HAART era) and 1.3 per 1,000 person-years in 2000-2006 (late HAART era) [31]. Similarly, a national multiple-cause-of-death database for the United States confirmed a decline in mortality from HIVassociated PML between the period 1992-1995 and the period 2002-2005; the decline was attributed to HAART [32]. Despite the observed decline in incidence, PML remains a significant central nervous system complication of HIV/AIDS.…”
Section: Pml With Aidsmentioning
confidence: 91%
“…By the mid-1990s approximately 4% of patents dying of acquired immunodeficiency syndrome (AIDS) had progressive multifocal leukoencephalopathy. With the routine use of highly active antiretroviral therapy in 1996, incidence and death rates of progressive multifocal leukoencephalpathy have gradually declined, though not reaching pre-epidemic levels (Christensen et al, 2010). The demyelinated foci show a loss of oligodendrocytes.…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 99%